2013
DOI: 10.1193/072511eqs184m
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of High-Voltage Transformer-Bushing Systems Incorporating Flexural Stiffeners I: Numerical Study

Abstract: High-voltage bushings have exhibited vulnerability during past earthquakes. The good performance of bushings mounted on a rigid base observed during shake table testing does not correlate well with their performance in the field. It is suspected that the seismic performance of high-voltage bushings is improved when mounted on a rigid base, as opposed to when mounted on more flexible cover plates of transformers. In this first of two companion papers, the seismic response of bushings was investigated numericall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 6 publications
3
22
0
Order By: Relevance
“…The additional flexural stiffeners on the cover plate were beneficial to the seismic response of the bushing, because it increased the fundamental frequency of the bushing close to that of rigid base condition . Considering the additional stiffeners, the maximum reduction in bending moment at the base of bushing was achieved in a range of 53% to 86% compared with the flexible cover plate . In addition, there are also many other methods used to mitigate the seismic responses of the bushing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional flexural stiffeners on the cover plate were beneficial to the seismic response of the bushing, because it increased the fundamental frequency of the bushing close to that of rigid base condition . Considering the additional stiffeners, the maximum reduction in bending moment at the base of bushing was achieved in a range of 53% to 86% compared with the flexible cover plate . In addition, there are also many other methods used to mitigate the seismic responses of the bushing.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Considering the additional stiffeners, the maximum reduction in bending moment at the base of bushing was achieved in a range of 53% to 86% compared with the flexible cover plate. [10] In addition, there are also many other methods used to mitigate the seismic responses of the bushing. The segmented high-damping rubber bearings were used in a test of transformerbushing system.…”
mentioning
confidence: 99%
“…During the analysis, the coupling system was subject to a larger PGA in the Y direction. Based on the analytical results, cumulative distribution functions were calculated for the probability of non‐exceeding (PoNE) 34 a prescribed maximum displacement at the bottom of the valve or at the top of the post insulator under the entire record set. Since the post insulator was already idealized as an SDOF oscillator, the displacement also represented the bending moment at the root section.…”
Section: Parametric Analysis Of the Seismic Response Of An Interconnementioning
confidence: 99%
“…Ersoy and Saadeghvaziri investigated the influences of the flexibility of the transformer's top plate on the dynamic responses of the bushing in SAP2000. Koliou provided the fragility curves of bushings with different mounted conditions and concluded that the additional stiffeners on the top plate of the transformer would be one of the most efficient retrofit approaches for reducing the bending moment at the base of the bushing Moreover, many/more techniques such as the additional stiffener, the increased preload, and the stiffer gaskets were also adopted to enhance the mounted conditions of the bushings, which would reduce the input motions at the base of the bushing. On the other hand, the base‐isolated technologies, such as the segmented high damping rubber bearings, the wire rope isolators (WRIs) and the friction pendulum systems (FPS) were also used for seismic protection of the bushings.…”
Section: Introductionmentioning
confidence: 99%